The interaction of feeding an eubiotic blend of essential oils plus 25-hydroxy-vit-D3 on performance, carcass characteristics, and dietary energetics of calf-fed Holstein steers - Latack, Brooke C.; Carvalho, Pedro H. V.; Zinn, Richard A. (Frontiers in Veterinary Science, 2022)
Essential oil blends have been identified as a potential alternative to ionophores in feedlot diets. Objective of this study was to evaluate the effects of a supplemental a blend of essential oils and 25-hydroxyvitamin D3 on growth performance, and carcass characteristics in calf-fed Holstein. Ninety Holstein steer calves (123 ±7 kg; 4 months old) were randomly assigned to 6 pens/treatment (5 steers/pen). Treatments were: 1) no additives (CON); 2) 30 mg/kg DM of monensin (MON); 3) 200 mg/kg DM of a mixture of essential oils plus 25-hydroxyvitamin D3 (EO+HYD). There were no treatment effects (P > 0.05) on cattle live weight, average daily gain (ADG), and dry matter intake (DMI). During the first 112 days, steers supplemented with EO+HYD had a greater (P ≤ 0.05) gain to feed ratio (G/F) than CON but similar (P > 0.05) to cattle supplemented with MON. There was no effect (P > 0.05) of dietary treatments on 112 to 286 d and the overall G/F ratio. Steers supplemented with EO+HYD had greater (P ≤ 0.05) estimated net energy for maintenance (NEm) and net energy for gain (NEg) than cattle fed the CON diet. Cattle supplemented with MON had an intermediate and similar (P > 0.05) NEm and NEg compared to the other two dietary treatments. However, when observed versus expected NEm and NEg were calculated, cattle supplemented with MON and EO+HYD had greater efficiency of dietary energy utilization than cattle fed the CON diet. Calf-fed Holstein steers supplemented with MON had greater (P < 0.05) fat thickness than EO+HYD supplemented steers, and both were intermediate (P ≥ 0.05) to that of cattle fed the CON diet. There were no other effects (P > 0.05) on kidney, pelvic and heart fat, longissimus area, marbling score, and retail yield. The health status of cattle and liver abscesses or liver scars at slaughter were similar (P > 0.05). We conclude that supplementing calf-fed Holstein steers with MON or EO+HYD for over 285 days increased dietary net energy utilization for maintenance and gain of the diet by 3 and 4%, respectively, compared to non-supplemented steers.